Strategi Implementasi Pengembangan Kurikulum Pendidikan Agama Islam di Akademi Kebidanan Prima Husada Kota Bogor - Ahmad Sukandar; Rohendi Rohendi; Muhammad Fikri Ghifari; Asyif Zaenal Muttaqin (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Curriculum development efforts at AKBID Prima Husada Bogor City are an urgency, and Insya Allah it will be included in the success of student teaching and learning activities (KBM) according to the times and included in the vision and mission of AKBID Prima Husada. Based on this, three problems become the main research studies, namely first, how is the implementation of the curriculum at AKBID Prima Husada Bogor City. Second, what is the curriculum development strategy at AKBID Prima Husada Bogor City. Third, what are the supporting and inhibiting factors for curriculum development at AKBID Prima Husada Bogor City. This research uses a qualitative approach with a descriptive type. Sources of data through interviews, observation, and documentation which are then analyzed in the form of data reduction, data presentation, and conclusions in accordance with the guidelines of qualitative research methodology.Keywords: Each word/phrase is separated by commas. he results of the study: first, the implementation of the curriculum at AKBID Prima Husada Bogor City is using the convergence curriculum with the name rainbow curriculum, namely the formal curriculum, and the tahfidz curriculum. Second, the curriculum development strategy is diversification by adding new products, namely the Hafid curriculum packaged with Reading and Writing the Qur'an (BTQ) and tahfidz (memorization of prayers from the Qur'an and Hadith). Third, the supporting and inhibiting factors for curriculum development at AKBID Prima Husada Bogor City are: Factors supporting flexibility, namely providing space and flexibility for stakeholders in the effort to develop curriculum at AKBID Prima Husada Bogor City. The inhibiting factor is the limited time in optimizing the Pelangi curriculum, and there are some students who do not have basic knowledge about BTQ learning. Keywords: Strategic Management, Curriculum Development